Condensation of 4-amino-3-(2-methoxy-4-propylphenoxymethylene)-(1h)-1,2,4-triazole-5-thione with some heterocyclic aldehydes. - Dinh, Nguyen Huu; Hien, Nguyen (Vietnam Journal of Chemistry, 2012)
A series of 6 imines were synthesized by condensing 4-amino-3-(2-methoxy-4-propylphenoxymethylen)-(1H)-1,2,4-triazole-5-thione with heterocyclic aldehydes. The structure of the imines were confirmed by UV, IR, 1H NMR and 13C NMR spectroscopy, in some cases,  2D NMR spectra are also used.